2009
DOI: 10.1038/sj.bjc.6604996
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a guaiac and an immunochemical faecal occult blood test for the detection of colonic lesions according to lesion type and location

Abstract: We investigated variations in sensitivity of an immunochemical (I-FOBT) and a guaiac (G-FOBT) faecal occult blood test according to type and location of lesions in an average-risk 50-to 74-year-old population. Screening for colorectal cancer by both non-rehydrated Haemoccult II G-FOBT and Magstream I-FOBT was proposed to a sample of 20 322 subjects. Of the 1615 subjects with at least one positive test, colonoscopy results were available for 1277. A total of 43 invasive cancers and 270 high-risk adenomas were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 20 publications
4
53
1
1
Order By: Relevance
“…6,8 Reported sensitivities in these studies have ranged from 40.5% to 94%. 7,8,21 Our results are likely more reflective of the expectations for a community-based program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,8 Reported sensitivities in these studies have ranged from 40.5% to 94%. 7,8,21 Our results are likely more reflective of the expectations for a community-based program.…”
Section: Resultsmentioning
confidence: 99%
“…5 Recent research, however, has indicated that FIT is more sensitive than fecal occult blood tests as well as being more convenient for patients. [6][7][8][9][10] Fecal immunochemical testing also offers advantages to clinical laboratories, including the potential for automation, the ability to customize the cutoff level to define a positive test, and improved cost-effectiveness. [11][12][13][14][15][16] Finally, by eliminating patients who do not need a colonoscopy, a FIT screening program may be more cost-effective than colonoscopybased screening.…”
mentioning
confidence: 99%
“…The advantage of q-FIT over g-FOBT lies in the recognition of a larger number of early cancers and adenomatous lesions 25 . Better results from this newer test will also play a favorable role in the psychological influence of both general practitioners and patients, which may help to decrease the relatively high proportion of unperformed colonoscopies despite a positive FOBT 28,29 . In the processing of liquid q-FIT kits, time-dependency is an important consideration compared to g-FOBT dry kits 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The improved stability offered by OCSensor compared with Magstream and the semiquantitative nature of the Magstream offer strong arguments in favor of OC-Sensor. Nevertheless, several studies have shown the good performance of Magstream in population surveys, even using only 1 sample at the manufacturer's threshold (17,18). Costs of the tests should also be considered, together with adaptation of screening programs to limit the effect of sensitivity of tests to temperature on their performances (12).…”
Section: Discussionmentioning
confidence: 99%